Synthesis and Biological Properties of Dihydro-Oxadiazine-Based Heterocyclic Derivatives - Ke, S.; Cao, X.; Liang, Y.; Wang, K.; Yang, Z. (Mini Reviews in Medicinal Chemistry, 2011)
Dihydro-oxadiazine and its derivatives have been demonstrated to be important heterocyclic scaffold platform with bioactive diversity, which present wide activities such as cardiovascular, antitumor, antibacterial, antimicrobial, acricidal, insecticidal, plant-growth regulating, chitin biosynthesis inhibitors and monoamine oxidase inhibition. Versatile features of dihydro-oxadiazine heterocycles have emerged, so the aim of the present paper was to review the recent advances of dihydro-oxadiazine-based heterocyclic derivatives mainly including synthesis and biological activities.
Keywords: insecticidal